Pengaruh Insentif Terhadap Prestasi Kerja Karyawan Hotel NDC Resort & SPA Manado (Productivity, 2021)
This study aims to determine the effect of incentives on employee performance at thet NDC Resort&Spa Manado. This type of research with a sample of 50 respondents. The sample is taken by saturated sample method. While the data analysis method used is the interview method and quisioner with the results of a simple linier regression equation tets with the help of SPSS 25 program tools. Based on the results of the study indicate that the incentive variable influences employee performance at the hotel NDC Resort&Spa Manado. Based on the calculation of the value (R) of 0,886 and the coefficient of determination (R2) of 0.807 this indicates that incentives provide an effect of 80.70% on employee work performance.